2020
DOI: 10.15252/emmm.202012628
|View full text |Cite
|
Sign up to set email alerts
|

A combination of two human monoclonal antibodies cures symptomatic rabies

Abstract: Rabies is a neglected disease caused by a neurotropic Lyssavirus, transmitted to humans predominantly by the bite of infected dogs. Rabies is preventable with vaccines or proper post‐exposure prophylaxis (PEP), but it still causes about 60,000 deaths every year. No cure exists after the onset of clinical signs, and the case‐fatality rate approaches 100% even with advanced supportive care. Here, we report that a combination of two potent neutralizing human monoclonal antibodies directed against the viral envelo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
33
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(37 citation statements)
references
References 38 publications
3
33
0
1
Order By: Relevance
“…It is not currently understood why AAV-CR4098 generates such low VNA titers compared with AAV-CR57. Newly developed mAbs such as RVC20 and RVC58 were found to have a higher potency than CR57 and CR4098 ( De Benedictis et al, 2016 ; de Melo et al, 2020 ; Hellert et al, 2020 ). Combined utilization of these mAbs may improve the effectiveness of postexposure prophylaxis.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It is not currently understood why AAV-CR4098 generates such low VNA titers compared with AAV-CR57. Newly developed mAbs such as RVC20 and RVC58 were found to have a higher potency than CR57 and CR4098 ( De Benedictis et al, 2016 ; de Melo et al, 2020 ; Hellert et al, 2020 ). Combined utilization of these mAbs may improve the effectiveness of postexposure prophylaxis.…”
Section: Discussionmentioning
confidence: 99%
“…A live RABV vaccine, on the other hand, is unlikely to be authorized for therapeutic use in human rabies patients. Most recently, de Melo et al (2020) showed that a combination of RABV-neutralizing antibodies (RVNA) RVC20 and RVC58 could rescue symptomatic mice post RABV infection by concomitantly administration of RVNA in the CNS through intracerebroventricular infusion, sheding a light for an effective rabies therapy in humans.…”
Section: Introductionmentioning
confidence: 99%
“…Drug cocktails containing Favipiravir, Ribavirin, Interferon α/β, a Caspase-1 inhibitor, a TNF-α inhibitor, a MAPKs inhibitor and human rabies immune globulin (HRIG) have been explored in mouse RABV models (Smreczak et al ., 2019) but no clear therapeutic effect was noted. A cocktail of two human monoclonal antibodies RVC20/RVC58 delivered directly into the brain could cure half of the symptomatic rabid mice in the research(de Melo et al ., 2020). One part of the current PEP protocol involves the injection of RIG around the exposure wound that can prevent the transport of the virus via the neuromuscular junction to the peripheral nervous system and subsequently to the CNS.…”
Section: Discussionmentioning
confidence: 99%
“…Access of antibodies to sites of viral replication in the clinical phase of the disease, when RABV is widely distributed in the CNS, is however problematic. Recently, de Melo et al ( 47 ) showed that continuous intracerebroventricular infusion for up to 20 days of two mAbs (RVC20 and RVC58) against the viral glycoprotein led to 56% survival of RABV-infected mice when initiated in the prodromal phase of the disease. Survival decreased to 33% when treatment was initiated one day later, in the early acute neurological phase.…”
Section: Therapeutic Approachesmentioning
confidence: 99%